Generation Y in Malaysian GLCs: relationship between Herzberg's motivation factors and job commitment / Nurul Nasuha Mohamed and Dr. Fadilah Puteh - Mohamed, Nurul Nasuha; Puteh, Fadilah (Dr.) (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Organization best HRM practices led towards committed employees, thus drive organizational success. In terms of organizational talents, Generation Y who is known as millennial generation is the new emerging workforce. However, several scholars termed Gen Y also known as millennial generation as disloyal workforces. Managing Gen Y effectively has puzzled many organizations. High turnover rate among millennial generation is now the concern of many organizations. Studies on what motivates Gen Y intrinsically towards job commitment in Malaysia are somewhat limited. Therefore, this paper intends to discover the relationship between Herzberg's motivation factors namely achievement, recognition, the work itself, responsibility, and opportunity for advancement and growth and job commitment among Generation Y in Malaysian Government Linked Companies (GLCs). A total of 400 Gen Y from top 10 Malaysian GLCs within Klang Valley was chosen as respondents. The findings revealed that there were strong relationship between achievement (r=0.730, p<0.01), recognition (r=0.704, p<0.01), the work itself (r=0.715, p<0.01), opportunity for growth and advancement (r=0.711, p<0.01) respectively with job commitment. However, responsibility (r=0.189, <0.01) was found to have a positive but weak relationship with job commitment. This study is hoped to enrich body of discussion on Gen Y and job commitment. Keywords: Generation Y, Herzberg's Motivation factors, Job commitment, Government Linked Companies (GLCs)